(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
An increasingly interconnected world, the ability to speak English has become less of a desirable skill and more of a necessity. No longer confined to the halls of academia, English has taken its place as the dominant language of global communication, opening doors to a wealth of opportunities for those who master it. Here’s why learning English is so crucial in the 21st century1 :